THE ROLE OF WOMEN IN TOURISM DEVELOPMENT IN THE BETAWI CULTURAL VILLAGE AREA OF SETU BABAKAN, JAGAKARSA SUB-DISTRICT, SOUTH JAKARTA - Wanda Rifdah, Ayu
Tourism is one of the important sectors in national and regional economic development, with great potential to create jobs and drive economic growth. In this sector, the role of women is a crucial aspect in supporting inclusive growth, improving community welfare, and strengthening the foundation of sustainable development. Therefore, women's participation is important in tourism development. One type of cultural tourism that is currently developing is the Betawi Cultural Village Area of Setu Babakan which is located in Srengseng Sawah Village, Jagakarsa Sub-District, South Jakarta City. This area is inhabited by the majority of the Betawi ethnic group with diverse involvement of women in it, where the role of women needs to be considered in tourism development. This study aims to identify the extent of the role of women in the development of tourism activities in the Betawi Cultural Village Area of Setu Babakan. To achieve the research objectives, the existing participation of women in tourism activities in the Betawi Cultural Village Area of Setu Babakan was analyzed by applying the theory of community participation with a qualitative descriptive analysis method. The results of this analysis are then used to identify the extent of women's participation based on the concept of community participation at each stage and then explain in which parts women play a role and play a lesser role in its implementation. The results of the study show that women's participation can be found in almost every aspect of tourism activities in the Setu Babakan Betawi Cultural Village Area, such as culinary tourism, cultural tourism, water tourism, and agro tourism. In every stage of participation, there is women's participation with various forms of roles. Women are given the opportunity to contribute and play a role in various fields according to their expertise and needs. Women play a major role in guest services, Betawi museum visitor services, souvenir shop services, regional dance arts, food and beverage provision, Betawi culinary workshops, and homestays.